Arabic as a foreign language (AFL): Northern UAE AFL Teachers’ Perceptions of the Integrated Approach - SALAMEH, WALID (2018)
The purpose of this study was to investigate how teachers perceive an integrated approach for students’ communicative competence in Arabic; and whether teachers are receptive to implementing an integrated approach in the TAFL classrooms and if they identify any potential obstacles to implementing an integrated approach at the private universities in the UAE Northern Emirates. The literature reveals that many studies investigated the students’ perceptions towards learning Modern Standard Arabic (MSA) but rarely tackled the teachers’ perceptions in this regard and what communicative Arabic instruction should involve. The design exploited in this study is a mixed methods research in two sequential phases: a quantitative phase followed by a qualitative phase. The source of the quantitative data was a survey adaptation of Arabic Teacher Survey (ATS). It is a 45-item survey of 40 participants. Due to the small size of the population who participated in the study, no significant relationships emerged between teachers’ perceptions of the integrated approach and its influence on communicative competence. In general, a positive perception of using the integrated approach arose as the right way to go about the teaching and learning of Arabic. The qualitative phase consisted of one-on-one interviews with five Arabic teachers to provide a more descriptive analysis of the survey data. The participating teachers’ perceptions of teaching both varieties are to some extent different in the order that they would teach the two varieties despite the fact that they all prefer to implement the integrated approach in their classes. The participants’ attributed the obstacles in the implementation of an integrated approach to the teachers’ mindset, insufficient materials, and choosing which colloquial dialect of Arabic to teach. This study sought to uncover the teachers’ perceptions of the integrated approach and its importance for the TAFL field in promoting the students’ communicative competence. Additionally, the study proposes an instructional design that accommodates the integrated approach besides recommendations for further research. The main purpose is to highlight the value of teaching both MSA and a spoken Arabic variety as the underpinning of communicative competence in Arabic.